An Assessment of a Community-Based, Forest Restoration Programme in Durban (eThekwini), South Africa - Lutendo F. Mugwedi (Forests, 2017)
The restoration of degraded forests to enhance biodiversity, ecosystem services, as well as climate change mitigation and adaptation is now a major priority in cities around the world. This study evaluated the success of the Buffelsdraai Landfill Site Community Reforestation Project in Durban, South Africa, by assessing ecological attributes. Measures of plant richness, diversity, vegetation structure, invasive alien plants (IAPs) and ecological processes were contrasted across a chronosequence of habitats under restoration (0-year-old, 3-year-old and 5-year-old) and compared with a reference forest habitat (remnant natural forest). Native tree species recruitment and vegetation structure increased with restoration age. Ecological processes, represented by the composition of pollination and seed dispersal traits in all of the habitats under restoration, were similar to the reference habitat. However, low tree density and an increase in IAP cover with an increase in restoration age were identified as threats to reforestation success. We recommend enrichment planting and an effective IAP management strategy to promote more rapid habitat restoration while reducing site maintenance costs. Enrichment planting should not only focus on increasing tree species density and richness, but also on the inclusion of species with missing pollination and seed dispersal categories.